Combining ability analysis for yield and yield contributing traits in maize (Zea mays L.) (Bangladesh Journal of Agricultural Research, 2019)
An experiment on combining ability was carried out with 21 crosses produced from 7×7 diallel cross without reciprocal for grain yield and yield contributing characters in maize. Analysis of variance for combining ability showed that mean square (MS) due to GCA & SCA were highly significant for all characters except GCA in plant height, cob length and 1000 grain weight and SCA in maturity and row/cob indicated that all but mentioned traits were governed by both additive and non-additive gene action. Variances due to GCA were higher for all characters except thousand grain weight revealed that the predominance of additive gene action for all characters except thousand grain weight. Parent CML 487 and Ki 21 were the best general combiner for yield and most of the yield contributing characters. Parent BMZ 57 & BMZ 15 were the best general combiner for dwarf & earliness in plant. Among all the crosses CML 473 × Ki 21, CML 487 × Ki 21 and CML 429 × BIL 182 exhibited significant positive SCA effect for grain yield. The cross CML 429 × BIL 182 may be considered as the best cross with recorded significant mean value and desired SCA for traits like 1000 grain weight, yield (t/ha), days to 50% pollen shedding, days to 50% silking, plant height, ear height and days to maturity. The promising single crosses with significant and positive SCA could be used for variety development after verifying them across locations.Bangladesh J. Agril. Res. 44(2): 253-259, June 2019